2015
DOI: 10.1021/acsami.5b03525
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Inverted Structure Perovskite Solar Cells via Oleamide Doping of PCBM Electron Transport Layer

Abstract: An amphiphilic surfactant, oleamide, was applied to dope the PCBM electron transport layer (ETL) of inverted structure perovskite solar cells (ISPSCs), resulting in a dramatic efficiency enhancement. Under the optimized oleamide doping ratio of 5.0 wt %, the power conversion efficiency of the CH3NH3PbIxCl(3-x) perovskite-based ISPSC device is enhanced from 10.05% to 12.69%, and this is primarily due to the increases of both fill factor and short-circuit current. According to the surface morphology study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
97
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 51 publications
3
97
0
1
Order By: Relevance
“…[29] As shown in Figure 5c, the Voc of the balanced device had a slower photovoltage decay than the reference, suggesting a lower charge carrier recombination rate and, thus, more balanced charge carrier transport. [41] Suppressed charge carrier recombination was also confirmed by the dark current measurements, [31] as shown in Figure 5d. The dark current densities of the balanced devices were almost two orders of magnitude lower than those of the reference ones.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…[29] As shown in Figure 5c, the Voc of the balanced device had a slower photovoltage decay than the reference, suggesting a lower charge carrier recombination rate and, thus, more balanced charge carrier transport. [41] Suppressed charge carrier recombination was also confirmed by the dark current measurements, [31] as shown in Figure 5d. The dark current densities of the balanced devices were almost two orders of magnitude lower than those of the reference ones.…”
mentioning
confidence: 57%
“…The PCE enhancement can be attributed to the increased Voc and FF, which benefit from the improved film morphology. [15,31] However, further increasing the concentration of PMMA did not improve the device performance, due to the insulating characteristic of PMMA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13,14 ] In fact, the electrical conductivities of a TiO x EEL in MS pero-HSCs and phenyl-C 61 -butyric acid methyl ester (PC 61 BM) EEL in PHJ pero-HSCs are several orders of magnitude lower than those of the hole-extraction layer (HEL) counterparts, [15][16][17][18][19][20] resulting in an inferior electron-collection effi ciency, lower shortcircuit current density ( J SC ), and lower fi ll factor (FF). [ 11,21 ] On the other hand, it has been reported that the contact between the perovskite layer and the EEL was poor due to the rough surface of the solution-processed perovskite layer, [ 22,23 ] which inevitably deteriorates the electron-extraction effi ciency, creates charge-carrier recombination, and simultaneously introduces large leakage currents. [24][25][26] In order to circumvent these problems, studies have been focused on the interfacial modifi cation of the contact between the EEL and the cathode.…”
mentioning
confidence: 99%